IMPLEMENTATION OF PHARMACIST PRACTICE PERMIT SERVICE POLICY AT THE HEALTH DEPARTMENT OF CENTRAL MALUKU REGENCY - Nurtati, Nurtati; Normawati, Normawati; Pattimukay, Hengky V. R. (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2024)
This study uses a quantitative method with a sample size of 60 people, utilizing primary and secondary data. Data collection was conducted through questionnaires, observations, and documentation, with data analysis performed using sociometric analysis tools. The results reveal that the implementation of the pharmacist practice permit service policy at the Health Department of Central Maluku Regency is evident through dimensions of consistency, transparency, accountability, fairness, participation, effectiveness, and efficiency, all showing high percentage levels. However, maximization is still needed to achieve the highest standard percentages. The implementation of this policy is influenced by factors such as communication, resources, disposition, and bureaucratic structure. These factors cumulatively contribute significantly to the implementation process. The remaining percentage for improvement can be targeted for follow-up maximization while prioritizing these influencing factors. The findings successfully explore and synergize theoretical and practical approaches, revealing the quantitative achievement levels of policy implementation. This has implications for strengthening and maximizing the implementation of the pharmacist practice permit service policy at the Health Department of Central Maluku Regency. In summary, the research demonstrates that the pharmacist practice permit service policy's implementation at the Health Department of Central Maluku Regency is highly effective in key dimensions but requires further optimization. Influencing factors such as communication, resources, disposition, and bureaucratic structure play a significant role in the successful implementation. The study's findings provide valuable insights for improving policy implementation, ensuring a more effective and efficient service delivery in the future.